2017
DOI: 10.3389/fnagi.2017.00069
|View full text |Cite
|
Sign up to set email alerts
|

Limited Effects of Set Shifting Training in Healthy Older Adults

Abstract: Our ability to flexibly shift between tasks or task sets declines in older age. As this decline may have adverse effects on everyday life of elderly people, it is of interest to study whether set shifting ability can be trained, and if training effects generalize to other cognitive tasks. Here, we report a randomized controlled trial where healthy older adults trained set shifting with three different set shifting tasks. The training group (n = 17) performed adaptive set shifting training for 5 weeks with thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 64 publications
2
26
0
Order By: Relevance
“…At present, the reason for these between-study differences in near-transfer effects, when differentiating between switch-and mixing-cost benefits, is unclear. The lack of any beneficial far-transfer effects is in line with previous recent task-switching training studies (e.g., Grönholm-Nyman et al, 2017;Kray & Fehér, 2017;Pereg et al, 2013;von Bastian & Oberauer, 2013;Zinke et al, 2012). The lack of any transfer to Stroop task performance is, perhaps, especially worthy of note.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…At present, the reason for these between-study differences in near-transfer effects, when differentiating between switch-and mixing-cost benefits, is unclear. The lack of any beneficial far-transfer effects is in line with previous recent task-switching training studies (e.g., Grönholm-Nyman et al, 2017;Kray & Fehér, 2017;Pereg et al, 2013;von Bastian & Oberauer, 2013;Zinke et al, 2012). The lack of any transfer to Stroop task performance is, perhaps, especially worthy of note.…”
Section: Discussionsupporting
confidence: 85%
“…However, it is important to note that there were no signs that the participants lost motivation to perform well on the trained task, as is reflected in the continued near-asymptotic high accuracy of responding across the training sessions in combination with the continuous decrease in RTs. Moreover, with a few exceptions (e.g., Anguera et al, 2013;Grönholm-Nyman et al, 2017;von Bastian & Oberauer, 2013) most training studies did not use adaptive training protocols, and overall the (non-) adaptive nature of the task does not seem to be critical to finding or not finding far-transfer effects. The same seems to be true for other measures that were taken in some studies to maintain motivation during training, such as by providing performance-dependent (monetary) feedback (e.g., Dörrenbächer et al, 2014;Strobach et al, 2012): training and/or transfer effects may still be limited despite such measures.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, studies on the trainability of cognitive flexibility already showed promising results (e.g. Grönholm-Nyman et al 2017;Zhao et al 2018). Further, current treatments for chronic pain such as mindfulnessbased interventions that aim at increasing EF and/or cognitive flexibility (Gallant 2016;Moynihan et al 2013;Ortner et al 2007) offer interesting new angles for future research on the relationship between EF and pain.…”
Section: Discussionmentioning
confidence: 99%
“…Two opposing scientific consensus statements on this matter, signed by hundreds of scientists each, were published in 2014 [ 8 , 9 ]. Various studies have found significant effects of cognitive training on far transfer tests (indicating effects on broader categories of cognitive functioning) [ 5 , 6 , 10 ] or that cognitive training does little more than to improve abilities on near transfer tests (indicating effects on tasks similar to the training), with no indication of far transfer [ 11 - 13 ]. With such discrepancy in the field, some researchers have turned to analysis of the methodology used in cognitive training studies and identified, among other issues, a failure to properly control for placebo effects [ 12 , 14 , 15 ], which are systematic factors related to, but separate from, the training itself that may have been a causal component of observed effects [ 16 ] (see the “What Is the Placebo Effect” section for a more detailed explanation).…”
Section: Introductionmentioning
confidence: 99%